(untitled) (Journal of Dhaka National Medical College & Hospital, 2023)
Background: High concentrations of homocysteine (Hcy) are supposed to be a potential risk factor for endothelial dysfunction characterized by preeclampsia (PE). Objectives: To determine the association of serum homocysteine (Hey) with PE. Methods: This cross-sectional study was conducted in the Department of Biochemistry, Dhaka Medical College, from July 2018 to June 2019. Thirty diagnosed case of preeclampsia and thirty apparently healthy pregnant women were selected according to the selection criteria from indoor and outpatient Department of Obstetrics and Gynaecology, Dhaka Medical College Hospital. Homocystine levels of all study subjects were estimated. The results were compared between these two groups. Results: Mean serum homocystine (Hey) level in pregnant women with PE was 13.74± 3.69 μmol/L and that of normal pregnancy was 5.89 ±1.70 μmol/L (p < 0.001). Serum Hey level in severe PE (16.04 ±3.26 μmol/L) was also significantly higher (p<0.001) compared to mild PE (10.73 ±1.20 μmol/L). Serum Hey level showed a significant positive relation (r-0.85, p<0.001) with PE. Conclusion: Scrum Hcy is increased in PE in comparison to healthy pregnancy. We suggest the assessment of serum Hey in all pregnant women as a part of antenatal checkup. J. Dhaka National Med. Coll. Hos. 2023; 29 (01): 37-40